Analisis Pengendalian Kualitas pada Produk Genteng Di CV. SDH Cilegon dengan Menggunakan Statistical Processing Control (SPC) - Febriyanto, Rendhy Rinaldy; Rosihin, Rosihin; Shofa, Mohamad Jihan (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2016)
CV. SDH Cilegon is engaged in construction services in carrying out production process activities; companies still experience product failures caused by humans, raw materials, machinery, methods and the environment and factors that often occur are humans because all production activities are carried out by humans, including machine operation. For work methods, returning to human factors again where the wrong approach to work can result in disability in production. Raw materials and the environment also affect the defects that arise. Sixty-three units dent failures that often occur; there are foreign bodies of 47 units, imperfect shape of 33 units, so the total number of defects is 143 units.